2023
DOI: 10.1002/macp.202200444
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Changes of Alginate and Polyacrylate Mixture Induced by Interactions of the Appended Units

Abstract: This study aims to analyze the physicochemical properties of solutions containing the mixture of polyacrylates functionalized with alkyl chains moieties and alginate (Alg) functionalized with 𝜷-cyclodextrins (CD). Functionalization of anionic polymers with host (CD) and guest units (alkyl chain) allow local host-guest interaction which determines discrete changes in properties of the resulted mixtures. The systems are investigated by surface tension, viscosity, and zeta-potential measurements, Fourier transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Similarly, we used EPR spectroscopy to evidence the host–guest interactions in solutions of polyacrylic acid functionalized with alkyl chains or adamantyl (guest) moieties and alginate functionalized with cyclodextrin (host) units. We found that the host–guest interactions between the appended units diminish the repulsive forces between the anionic polymers and influence the formation of inter-coils of polyacrylic acid [ 22 ]. By using the same approach, in this study, we aim to link the local information provided by EPR measurements with the overall properties of the alginate/chitosan systems that can be obtained by rheological measurements and IR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we used EPR spectroscopy to evidence the host–guest interactions in solutions of polyacrylic acid functionalized with alkyl chains or adamantyl (guest) moieties and alginate functionalized with cyclodextrin (host) units. We found that the host–guest interactions between the appended units diminish the repulsive forces between the anionic polymers and influence the formation of inter-coils of polyacrylic acid [ 22 ]. By using the same approach, in this study, we aim to link the local information provided by EPR measurements with the overall properties of the alginate/chitosan systems that can be obtained by rheological measurements and IR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%